Efficacy of Adapalene 0.1% Versus Tretinoin 0.025% Cream as Treatment of Mild Acne Vulgaris - Sarah Diba; Zahra Ayu Lukita Sari; Muhammad Athuf Thaha (HM Publisher, 2020)
Abstract Introduction: Acne vulgaris (AV) is a chronic inflammatory of the pilosebaceous unit. Topical retinoid is a mainstay of mild AV first-line treatment. Aim of study: To assess the efficacy of topical retinoid for the treatment of mild AV. Method: The randomized double-blind clinical trial was conducted from June to September 2019 at Dr. Mohammad Hoesin General Hospital Palembang. A total of 70 mild AV patients who fulfilled inclusion criteria were enroled consecutively. Patients randomly treated with adapalene 0.1% cream or tretinoin 0.025% cream and evaluated every 2 weeks for 8 weeks to examine the number of AV lesion (inflammation, non-inflammation and total lesion). Result: There are reduction in number of inflammatory and non-inflammatory lesions at both groups but only inflammatory lesion was statistically significant (p <0.05). Total lesions also decrease in adapalene and retinoin group (21.66 vs 5.75, 22.21 vs 7.96, respectively) and statistically significant (p <0.05). Conclusion: Adapalen 0.1% cream showed non-inferiority to tretinoin 0.025% cream in efficacy, especially in the reduction of non-inflammatory and total lesions.